Leri's pleonosteosis, a congenital rheumatic disease, results from microduplication at 8q22.1 encompassing GDF6 and SDC2 and provides insight into systemic sclerosis pathogenesis. Issue 6 (17th January 2014) - Banka, Siddharth; Cain, Stuart A; Carim, Sabrya; Daly, Sarah B; Urquhart, Jill E; Erdem, Günhan; Harris, Jade; Bottomley, Michelle; Donnai, Dian; Kerr, Bronwyn; Kingston, Helen; Superti-Furga, Andreas; et al.
Abstract : Objectives: Leri's pleonosteosis (LP) is an autosomal dominant rheumatic condition characterised by flexion contractures of the interphalangeal joints, limited motion of multiple joints, and short broad metacarpals, metatarsals and phalanges. Scleroderma-like skin thickening can be seen in some individuals with LP. We undertook a study to characterise the phenotype of LP and identify its genetic basis. Methods and results: Whole-genome single-nucleotide polymorphism genotyping in two families with LP defined microduplications of chromosome 8q22.1 as the cause of this condition. Expression analysis of dermal fibroblasts from affected individuals showed overexpression of two genes, GDF6 and SDC2, within the duplicated region, leading to dysregulation of genes that encode proteins of the extracellular matrix and downstream players in the transforming growth factor (TGF)-β pathway. Western blot analysis revealed markedly decreased inhibitory SMAD6 levels in patients with LP. Furthermore, in a cohort of 330 systemic sclerosis cases, we show that the minor allele of a missense SDC2 variant, p.Ser71Thr, could confer protection against disease (p<1×10 −5 ). Conclusions: Our work identifies the genetic cause of LP in these two families, demonstrates the phenotypic range of the condition, implicates dysregulation of extracellular matrix homoeostasis genes in its pathogenesis, and highlights the link between TGF-β/SMAD signalling, growth/differentiation factor 6 and syndecan-2. We propose that LP is an additional member of the growing 'TGF-β-pathies' group of musculoskeletal disorders, which includes Myhre syndrome, acromicric dysplasia, geleophysic dysplasias, Weill–Marchesani syndromes and stiff skin syndrome. Identification of a systemic sclerosis-protective SDC2 variant lays the foundation for exploration of the role of syndecan-2 in systemic sclerosis in the future.